2018
DOI: 10.1186/s12985-018-0950-6
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of age-specific pattern of coronavirus infection in Lyle’s flying fox (Pteropus lylei) in Thailand

Abstract: BackgroundBats are natural reservoirs for several highly pathogenic and novel viruses including coronaviruses (CoVs) (mainly Alphacoronavirus and Betacoronavirus). Lyle’s flying fox (Pteropus lylei)‘s roosts and foraging sites are usually in the proximity to humans and animals. Knowledge about age-specific pattern of CoV infection in P. lylei, prevalence, and viral shedding at roosts and foraging sites may have an impact on infection-age-structure model to control CoV outbreak.MethodsP. lylei bats were capture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 31 publications
8
64
0
Order By: Relevance
“…Similar seasonality of coronavirus shedding has been observed in Germany, Australia, Thailand, China, and Ghana (West Africa). In the specific species involved in these previous studies, higher coronavirus shedding and viral loads were detected weeks after the birth pulse [47][48][49][50][51][52]85]. Further, and consistent with our results, detection of higher levels of coronavirus in juveniles has been reported in micro-as well megabats from Africa, Asia, Europe, and North and South America [22,48,50,[86][87][88][89].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Similar seasonality of coronavirus shedding has been observed in Germany, Australia, Thailand, China, and Ghana (West Africa). In the specific species involved in these previous studies, higher coronavirus shedding and viral loads were detected weeks after the birth pulse [47][48][49][50][51][52]85]. Further, and consistent with our results, detection of higher levels of coronavirus in juveniles has been reported in micro-as well megabats from Africa, Asia, Europe, and North and South America [22,48,50,[86][87][88][89].…”
Section: Discussionsupporting
confidence: 91%
“…If coronavirus shedding by bats follows temporal patterns that are generalizable across species and locations, then mitigation strategies targeting the prevention of human exposure and potential spillover could be directed toward high-risk periods, through mechanisms that can also support bat-human coexistence and the provision of bat ecosystem services. Previous research has focused on viral identification in specific locations and in few species [47][48][49][50], resulting in a limited representation of viral dynamics in association with few ecological settings, biological traits, and reproductive strategies. Additionally, few studies of coronavirus shedding patterns have employed statistical models and, in consequence, the potential complex web of factors and causal relationships that may determine this process has not been fully explored.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, CoV prevalence in bat populations may significantly vary across seasons, as found in Mozambique with higher prevalence during the wet season than in the dry season. Several studies on bat CoV have indeed shown significant variations in the temporal infection dynamic of CoV in bats, potentially associated with bat parturition [32][33][34] .…”
Section: Discussionmentioning
confidence: 99%